First Report on Three Cases of Monkey pox in Nord Ubangi Province (Democratic Republic of the Congo) - Koto-te-Nyiwa Ngbolua; Guy Kumbali Ngambika; Blaise Mbembo-wa-Mbembo; Kohowe Pagerezo Séraphin; Kogana Kapalata Fabrice; Gédéon Ngiala Bongo; Masengo Ashande Colette; Djolu Djoza Ruphin (Britain International for Academic Research (BIAR) Publisher, 2020)
Monkey pox is a rare viral zoonotic disease of which clinical manifestations are similar to smallpox, it is transmitted to humans by direct contact with the body of an infected animal, but the transmission can also be human-to-human. The Democratic Republic of Congo is the most endemic country in the world where almost all provinces are affected by this scourge. However, in the administrative configuration currently, monkey pox has not been detected in Nord Ubangi province yet. This cross-sectional study focuses on three cases of patients diagnosed with monkey pox virus at Businga General Hospital in Nord Ubangi province. The findings show that all the three patients were male with a primary education level and their average age was 9±3.46 years. They had some epidemiological characteristics specific to monkey pox, including high fevers, rashes, pruritus and abdominal pain. After two weeks of symptomatic treatment, each patient was able to get out without further complications. For the best of our knowledge, this is the first report on the cases of Monkey pox in Nord Ubangi Province.